Covid 19 Neologisms in English - Bharati, Padam Lal (Saptagandaki Journal, 2020)
The purpose of this article is to explore and analyse some of the English words and expressions that have emerged or come into new light with the spread of Covid-19. Most of the words and expressions analyzed come from the author’s own observation of their occurrence in the media and some others are borrowed from the sources that he has read and reviewed. The article is based on the theory of neologism as discussed in Plag (2003), Akmajian, De[1]mers, Farmer and Harnish (2010) and Yule (2017). It lists and categorizes common coronavi[1]rus related neologisms and analyses their formation processes and use. Etymology of some of the terms has been traced as far as possible.